Valence band tomography of wurtzite GaN by spectroscopic ellipsometry. (30th August 2018) - Feneberg, Martin; Winkler, Michael; Lange, Karsten; Wieneke, Matthias; Witte, Hartmut; Dadgar, Armin; Goldhahn, Rüdiger
Abstract: The effective hole masses of wurtzite GaN are determined experimentally by an all-optical method. Therefore, we measure interband transitions as a function of the degenerate free-electron density and analyze the different many-body contributions arising from the Burstein–Moss effect and band-gap renormalization. When the known anisotropic effective electron mass is taken into account, the shape of the valence band can be reconstructed. Here, nonpolar GaN thin films doped with germanium or silicon at 9 × 10 18 ≤ n ≤ 1.5 × 10 20 cm −3 are investigated. Effective hole masses of, for the A valence band and for the B valence band are found (for 0.3 nm −1 < | k | < 2 nm −1 ) .